Sorghum flour's effect on improving plasma lipid profile and atherogenic index in diabetic rats - Dewi Setyowati; Aniq Nailil Muna; Anis Septiyani; Nurmasari Widyastuti; Ani Margawati; Martha Ardiaria; A. Fahmy Arif Tsani (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Dyslipidemia increases the risk of coronary heart disease in people with diabetes. Increased consumption of foods substantial in fiber and antioxidants, such as sorghum, can help people with diabetes manage their lipid profiles and improve insulin sensitivity. The study aimed to evaluate how sorghum flour affected diabetic rats' plasma atherosclerosis index (IAP) score and blood lipid profile. A randomized control design was used for the research's experimental methodology. In 2019, the study was carried out at P3G Laboratory UGM. 18 male Wistar rats served as the subjects and were separated into three groups: treatment (P) (5 g/mouse/day for 28 days), positive control (K+), and negative control of sorghum flour (K-). By administering nicotinamide and streptozotocin (STZ), the DM rat model was created (NA). The GPO-PAP method was used to measure TG levels. Total cholesterol, low-density lipoprotein, and high-density lipoprotein were all measured using CHOD-PAP. The log (TG/HDL) ratio (IAP) calculated the plasma atherosclerosis index. Paired T-tests, Wilcoxon, Anova, and Kruskal-Wallis, were used to evaluate the data. According to the findings, there were significant changes in the groups' baseline and post-intervention levels of total cholesterol (p=0,003), triglycerides (p=0,002), low-density lipoprotein (p=0,003), high-density lipoprotein (p=0,002), and IAP (p=0,001). In conclusion, feeding DM rats sorghum flour altered their blood lipid levels and plasma atherosclerosis index (IAP). Their LDL, triglycerides, and total cholesterol can all be reduced with a daily intake of 5 g per person.